Enzymatic Deracemization of (R,S)-Ibuprofen Ester via Lipase-catalyzed Membrane Reactor - Lau, Sie Yon; Gonawan, Fadzil; Kamaruddin, Azlina; Uzir, Mohamad (American Chemical Society, 2013)
Ibuprofen (isobutyl-propanoic-phenolic acid) is a chiral drug which essentially well-known for its analgesic, antipyretic and anti-inflammatory effects. In the present work, an enzymatic membrane reactor (EMR) has been developed for the production of optically pure (S)-ibuprofen acid. The EMR is equipped with a multi-tubular fixed bed racemization unit to enhance the enzymatic deracemization of (R,S)-ibuprofen ester. Several process parameters such as enzyme loading, racemization catalyst loading, reaction temperature, buffer pH as well as the flow rate were investigated. These experimental results were then compared with the proposed process model. It was found that the experimental data were in good agreement with the theoretical results. The optimum condition of the lipase-catalyzed dynamic kinetic resolution (DKR) using the EMR could give 96-98% conversion with 97-99% of product enantiomeric excess (eep).